Online Gambling as an Economic Escape: A Qualitative Study of the Community in Serang City - Helmas Septiyo Hadi; Dadang; Sena Atmaja; Dindin Aminudin; Ingkak Chintya Wangsih (www.amertainstitute.com, 2025)
The phenomenon of online gambling has seen significant growth in Indonesia, including in Serang City, particularly amid economic pressures. This study aims to explore in depth how the people of Serang City use online gambling as an economic escape. A qualitative approach was employed with a case study method, involving in depth interviews with 15 participants who actively engage in online gambling. The results indicate that online gambling is seen as an economic alternative due to financial pressures, limited job opportunities, and easy access to technology. The study also reveals the presence of addiction cycles and social vulnerability resulting from this practice. These findings are interpreted through the lens of Strain Theory (Merton) and Rational Choice Theory, which explain individual actions in response to economic constraints. The implications of this research suggest the need for strengthened digital literacy, law enforcement, and community-based interventions.